b - Pears,Richard; Shields, Graham (b)
"Now in its twelfth edition, this essential resource is the go-to text for students and authors who want to accurately reference sources and avoid plagiarism in their work"
Includes bibliographical references and index.
Keywords: Bibliographical citations